Investigation on Soil Strength and Microstructure of Palm Oil Boiler Ash with Sodium Hydroxide and Sodium Silicate as Alkaline Solution - Zainuddin, Atiqah Najwa; Mukri, Mazidah; Norbaya Sidek (International Journal of Sustainable Construction Engineering and Technology, 2022)
Palm oil boiler ash is a type of industrial waste from palm oil production, which abundantly disposed on landfill, and contaminate the soil and environment. Recently, boiler ash as a by-product is introduced as an additive in chemical stabilization, known as geopolymer. An alkaline solution functions to activate the silica-alumina structure bonding to replace the Ordinary Portland Cement in concrete application but few in soil stabilization study. This study investigates the strength of laterite with a geopolymer. Boiler ash was chosen as source material, with sodium hydroxide and sodium silicate mixed at a ratio of 1:2. Unconfined compressive test (UCT) and SEM were conducted for laterite soil with different geopolymer percentages. The test was conducted by adding a different geopolymer percentage at 0%, 5%,10%,15%, and 20% mixed with laterite soil. The soil sample was cured for seven days for an unconfined compression test (UCT). The result shows that the highest compressive strength was obtained at 15% of geopolymer in laterite soil at 340kPa. SEM tests show that the increased compressive strength was attributable to the 15% of the geopolymer, which had a compact and dense structure and less unreacted raw materials. In conclusion, the results indicated that 15% of geopolymer gives optimum value in enhancing laterite properties’ strength. The ï¬ndings support boiler ash usage as by-products in geopolymers’ production for potential use in soil strength stabilization.